Silicide-based alloy material and element using same
The silicide-based alloy material, with its specific composition and crystalline phases, addresses the challenges of achieving high thermoelectric conversion efficiency and minimizing environmental impact, particularly in low-temperature ranges.
Patent Information
- Application Number
- JP2021042155
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-16
- Publication Date
- 2025-05-15
- Estimated Expiration
- 2041-03-16
AI Technical Summary
Current thermoelectric materials face challenges in achieving high thermoelectric conversion efficiency while minimizing environmental impact and cost, especially in medium temperature ranges where existing materials contain toxic elements and have limited performance.
A silicide-based alloy material containing boron, primarily composed of silicon and ruthenium, with specific atomic ratios and a plurality of crystalline phases, is developed to enhance both Seebeck coefficient and electrical conductivity, thereby improving thermoelectric performance.
The silicide-based alloy material achieves high thermoelectric conversion efficiency in low-temperature ranges, reducing environmental impact and cost, while maintaining excellent thermoelectric properties across a broad temperature range.
Smart Images

Figure 0007676844000001 
Figure 0007676844000002 
Figure 0007676844000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicide-based alloy material and an element using the same. [Background technology]
[0002] Thermoelectric power generation using waste heat has long been known as a candidate for renewable energy. Currently, Bi2Te3 is in practical use for waste heat below 200℃, but Bi-Te-based materials have problems in that both Bi and Te are expensive, and Te is extremely toxic. For this reason, there is a demand for thermoelectric conversion elements that can reduce power generation costs and environmental impact.
[0003] In addition, the exhaust heat generated by waste incineration plants and automobiles is in the temperature range of about 200°C to 600°C (hereinafter referred to as the medium temperature range), which is higher than the above-mentioned temperatures. Materials used in these temperature ranges contain highly toxic elements such as Sb and As, which poses a large environmental burden.
[0004] Alloy materials combining metal and silicon have been attracting attention as high-performance thermoelectric materials for medium temperature ranges with low environmental impact. In particular, Mg2Si is known (see Patent Document 1, for example), and a mixture of Mg2Si and CaMgSi has been proposed as a p-type thermoelectric material using homologous elements (see Patent Document 2, for example). However, the Seebeck coefficient at 400°C is as low as 70 μV / K or less, and thermoelectric properties sufficient for practical use have not been obtained.
[0005] Therefore, it has low environmental impact and low cost, and can be used in a temperature range including temperatures above 200°C. In the above, there is a demand for thermoelectric conversion materials that can provide high thermoelectric conversion efficiency.
[0006] Non-Patent Documents 1 and 2 report an alloy of silicon and ruthenium that has high electrical conductivity and Seebeck coefficient in the medium temperature range; however, these disclosures concern a single crystal sample produced by the FZ method, and the thermal conductivity at room temperature was 5.0 W / K m. The figure of merit Z, which is an index of performance in thermoelectric conversion, and the absolute temperature T were low.
[0007] In addition, Non-Patent Document 3 shows that ruthenium and silicon show relatively high thermoelectric conversion efficiency in the medium temperature range (400°C to 600°C). However, in the low temperature range below 200°C, it is not possible to improve both the electrical conductivity and the Seebeck coefficient, and high thermoelectric conversion efficiency has not been achieved. In Non-Patent Document 3, an alloy with a ruthenium to silicon ratio of 1:1 is produced by arc melting, and its electrical properties and thermal properties are measured, but this is limited to a temperature range below 300K, and no information is given about the detailed structure of the obtained alloy other than the crystal phase.
[0008] Furthermore, in Non-Patent Document 4, an alloy with a ruthenium and silicon ratio of 1:1 was prepared by the same method as in Non-Patent Document 3, and its thermoelectric performance was measured. It is disclosed that the Seebeck coefficient at around 100°C was 250 μV / K and the electrical conductivity was approximately 6 × 10E-3 Ω cm. However, as in Non-Patent Document 4, no information is given about the detailed structure of the obtained alloy other than the crystal phase.
[0009] Patent Document 3 reports a silicide-based alloy material of silicon and ruthenium. Patent Document 3 does not disclose the inclusion of boron, and higher thermoelectric properties than those of Patent Document 3 are required. Here, T is the absolute temperature, and the figure of merit Z is defined by the following equation.
[0010]
number
[0011] S is the Seebeck coefficient (V / K), σ is the electrical conductivity, which is the reciprocal of the electrical resistance (Ω·m), and κ is the thermal conductivity (W / K·m). The numerator of Z (the product of the square of S and σ) is the power factor (W / K 2 It is called ·m).
[0012] In addition, (power factor / thermal conductivity) x temperature (K: Kelvin) is called thermoelectric conversion performance.
[0013] The inventors have discovered that by controlling the crystal grain size and creating a silicide-based alloy material containing multiple crystal phases and mainly composed of silicon, ruthenium, and boron, it is possible to improve both the Seebeck coefficient and the electrical conductivity, thereby enhancing thermoelectric performance. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP 2002-368291 A [Patent Document 2] JP 2008-147261 A [Patent Document 3] Patent Publication No. 2021-20842 [Non-patent literature]
[0015] [Non-Patent Document 1] L.Ivanenko et al. 22nd International Conference on Thermoelectrics 2003 157-160 [Non-Patent Document 2] L.Ivanenko et al.Microelectronic Engineering 70(2003) 209-214 [Non-Patent Document 3] B. Buschinger et al. Journal of Alloys and Compounds 256(1997) 57-60 [Non-Patent Document 4] H.Hole et al. Journal of Alloys and Compounds 278(1998) 39-43 Summary of the Invention [Problem to be solved by the invention]
[0016] An object of the present invention is to develop a silicide-based alloy material capable of reducing the environmental load and achieving high thermoelectric performance, and an element using the same. [Means for solving the problem]
[0017] An embodiment of the silicide-based alloy material according to the present invention has the following characteristics. (1) A silicide-based alloy material containing silicon and ruthenium as main components and boron, in which the atomic ratios of the elements constituting the alloy material are Si, Ru, and B, respectively. 45atm%≦Si / (Ru+Si+B)≦49.5atm% 45atm%≦Ru / (Ru+Si+B)≦49.5atm% 1atm%≦B / (Ru+Si+B)≦10atm% A silicide-based alloy material. (2) The silicide-based alloy material according to (1), which is a silicide-based alloy material containing silicon and ruthenium as main components and containing boron, and has a plurality of crystal phases in its structure. (3) A silicide-based alloy material according to (1) or (2), which is mainly composed of silicon and ruthenium and contains boron, and has at least two or more types of crystal phases selected from space groups 198, 64, 60, and 59 in its structure. (4) A thermoelectric conversion element using the silicide-based alloy material according to any one of (1) to (3).
[0018] The present invention will be described in detail below.
[0019] The silicide-based alloy material of the present invention is a silicide-based alloy material mainly composed of silicon and ruthenium and containing boron, and the atomic ratio of the elements constituting the alloy material is as follows, when the contents of silicon, ruthenium, and boron are Si, Ru, and B, respectively: 45atm%≦Si / (Ru+Si+B)≦49.5atm% 45atm%≦Ru / (Ru+Si+B)≦49.5atm% 1atm%≦B / (Ru+Si+B)≦10atm% and It is suitable as a thermoelectric conversion material (low-temperature thermoelectric material) in the temperature range of 200° C. or less. 47.5atm%≦Si / (Ru+Si+B)≦49.5atm% 47.5atm%≦Ru / (Ru+Si+B)≦49.5atm% 1atm%≦B / (Ru+Si+B)≦5atm% and most preferably 48.5atm%≦Si / (Ru+Si+B)≦49.5atm% 48.5atm%≦Ru / (Ru+Si+B)≦49.5atm% 1atm%≦B / (Ru+Si+B)≦3.5atm% It is.
[0020] This is because, within the above-mentioned composition range, a silicide-based alloy material containing silicon and ruthenium as its main components and boron exhibits a semiconductor crystal phase with excellent thermoelectric conversion performance for use as a low-temperature thermoelectric material; if the composition is outside this range, a crystal phase with metallic physical properties will appear in the silicide-based alloy material, or a crystal phase with a different ratio of ruthenium to silicon will appear, causing a decrease in performance, resulting in a significant deterioration in thermoelectric conversion performance.
[0021] The silicide-based alloy material for low-temperature thermoelectric materials preferably has a structure having a plurality of crystal structures with different ratios of ruthenium and silicon. More preferably, the structure contains at least two or more crystal structures selected from space groups 198, 64, 60, and 59. In particular, in order to achieve high thermoelectric performance in the low-temperature range of 100°C or less, it is preferable that the structure contains a crystal structure selected from space groups 198, 60, and 59.
[0022] The silicide-based alloy material of the present invention may contain unavoidable trace amounts of impurities, such as metal elements other than Si, Ru, and B, and compounds such as oxides of these metal elements.
[0023] Next, a method for producing the silicide-based alloy material of the present invention will be described.
[0024] The manufacturing method of the present invention preferably includes a step of synthesizing an alloy from ruthenium, silicon and boron, a step of pulverizing or quenching the alloy to obtain a powder, as the case may be, and a step of sintering the alloy powder by hot pressing at a sintering temperature of 900°C to 1850°C.
[0025] First, in the process of synthesizing an alloy from ruthenium, silicon, and boron, ruthenium, silicon, and boron are prepared in a predetermined ratio, and are melted in advance in an arc melting furnace to synthesize boron-containing ruthenium silicide. This is for the purpose of removing impurities in the powder and for the purpose of refining the alloy structure described below. Furthermore, as a melting condition, it is preferable to treat with high power for a short time rather than melting with low discharge power for a long time. The current amount is preferably 30 A / g or more, more preferably 200 A or more, in terms of current value per unit sample amount. A current value of less than 30 A / g is insufficient to melt ruthenium, and as a result, it is difficult to make a homogeneous alloy, which is not preferable.
[0026] The alloy obtained under the above preferred conditions is an alloy of boron-containing ruthenium silicide.
[0027] The subsequent step of crushing the alloy into a powder or quenching, as the case may be, reduces the particle size of the resulting powder.
[0028] When pulverizing, it is preferable to perform the pulverization in an inert gas atmosphere so as not to increase the amount of oxygen contained after the synthesis of the alloy. This is because it is possible to prevent oxidation of the powder surface and keep the amount of oxygen contained low. Furthermore, the pulverization method can control the structure when the silicide-based alloy material is obtained. As a method for pulverization and granulation, methods such as mortar pulverization, ball milling, jet milling, bead milling, spray drying, and gas atomization can be used. The primary particle size of the powder obtained at this time is preferably as small as possible. In addition, the average granulated particle size of the granulated powder when granulated is not particularly limited, but it is more preferable that it is about 10 to 100 μm in consideration of handling and the like.
[0029] When quenching, the molten silicide alloy material is sprayed onto a water-cooled copper roller rotating at 3000 rpm, which allows it to instantly solidify from the molten state and become a thin ribbon (quenched ribbon). In this case, the cooling rate is approximately 8×10 5 It may also be K / s.
[0030] Finally, in the sintering process in which the alloy powder is hot-pressed at a sintering temperature of 900°C to 1850°C, sintering methods that can be used include an atmospheric controlled furnace, hot pressing, which is a type of pressure sintering, and spark plasma sintering.
[0031] An example of spark plasma sintering, which is a type of pressure sintering, is explained below. Spark plasma sintering is a device that applies heat to a sample by applying pressure to the powder while passing electricity through it, and sintering proceeds. Uniaxial pressure is applied while heating to assist diffusion during firing, making it easier to sinter materials that are difficult to sinter, such as those with low diffusion coefficients or large particle sizes, such as metals. Furthermore, since sintering is performed by passing electricity directly through the sample, sintering can be performed in a shorter time than sintering using external heating, the increase in crystal grain size of the sintered body structure is suppressed, and high mechanical strength can be maintained.
[0032] From the above, it was found that the density was improved by firing using the spark plasma sintering method compared to conventional methods, and the theoretical densities of the RuSi crystal phases of space group 198 and space group 221 were 8.44 g / cm3, respectively. 3 , 8.04g / cm 3 This makes it possible to obtain a silicide-based alloy material with a relative density of 80% or more. The firing temperature in the treatment is 900°C to 1450°C, and preferably 1000°C to 1400°C. At temperatures lower than 900°C, sintering does not proceed and the density increases only to the same extent as the density of the compact. Also, if firing is performed at temperatures higher than 1450°C, RuSi melts and the alloy adheres to the die of the spark plasma sintering device, which may reduce the yield.
[0033] Here, in the case of silicide-based alloy materials suitable for low-temperature thermoelectric conversion materials, the temperature is preferably 1200° C. or higher or 1400° C. or lower, since this makes it easier to control the generation ratio of space group 60 and to obtain high thermoelectric conversion performance.
[0034] The pressure during firing is preferably 10 MPa to 100 MPa. This is because it improves the density of the silicide-based alloy material and allows it to withstand use in commonly used carbon dies. Furthermore, by controlling the pressing pressure, it is possible to change the crystal phase generated in the silicide-based alloy material. In particular, when producing a silicide-based alloy material suitable for low-temperature thermoelectric conversion materials, a pressure of 10 MPa to 75 MPa is particularly preferable because it is easy to achieve thermoelectric conversion performance.
[0035] The sintering is preferably carried out in an oxygen-free inert gas atmosphere such as nitrogen or argon, or in a vacuum.
[0036] The holding time at the firing temperature in the spark plasma sintering process is not particularly limited, but it is preferably 3 minutes or more. If the holding time is short, the inside cannot be heated uniformly and it is difficult to maintain the shape as a polycrystalline body. On the other hand, the holding time is preferably 10 minutes or less. An extension of the holding time may induce an increase in the grain size, which may result in an increase in the thermal conductivity.
[0037] The silicide-based alloy material of the present invention may be processed to a predetermined size. The processing method is not particularly limited, and a surface grinding method, a rotary grinding method, a cylindrical grinding method, or the like can be used. By using these methods, it is possible to process it into a shape suitable for use as a thermoelectric conversion element.
[0038] The silicide-based alloy material of the present invention is preferably used as a thermoelectric conversion element.
[0039] Thermoelectric conversion elements are made using p-type and n-type semiconductors. Therefore, it is preferable that the semiconductor material used can be controlled to be p-type or n-type. In the present invention, it is possible to control the p-type or n-type by adding a specific element to an alloy of silicon, ruthenium, and boron.
[0040] An example of a method for manufacturing a thermoelectric conversion element using the above silicide-based alloy material will be described below. The p-type and n-type silicide alloy materials are placed in parallel so that they do not touch each other, and an electrode bridges the upper parts. When these structures are used to create a II-shaped element, the upper part of the element is in contact with high temperatures, and when heated, a temperature gradient occurs between the upper and lower parts of the element, and a current is generated from the potential difference caused by the Seebeck effect according to the temperature difference ΔT (=TH-TL) at that time. Therefore, by attaching electrodes to the p-type and n-type silicide alloy materials at the bottom of the element and forming a circuit via an appropriate resistor, it can be used as a battery. Effect of the Invention
[0041] By using the silicide-based alloy material of the present invention, it is possible to fabricate a highly efficient thermoelectric conversion element having improved Seebeck coefficient and electrical conductivity at a relatively low temperature. EXAMPLES
[0042] Examples of the present invention will be described below, but the present invention is not limited to these examples. (Method of measuring crystal phase) The crystalline phase was identified from the diffraction peaks obtained by X-ray diffraction measurement. (Method of measuring composition) Quantitation was performed by ICP-MS mass spectrometry. (Method of measuring electrical characteristics) The measurements were carried out using a Hall effect measuring device (ResiTest8400, manufactured by Toyo Corporation). (Method of measuring Seebeck coefficient) A Seebeck coefficient measurement system (ResiTest8400 option, manufactured by Toyo Corporation) was attached to the Hall effect measurement device, and measurements were performed. (Method of measuring thermal conductivity) The measurements were carried out using a laser flash thermal conductivity measuring device (Advance Riko Co., Ltd., TC1200-RH type). (Occupancy rate of each crystal phase) The proportion of each crystal phase in the sintered compact structure was calculated using 300x images taken with an electron backscatter diffraction (EBSD: Oxford Instruments Symmetry) attached to a field emission scanning electron microscope (JEOL JSM-iT800).
[0043] Example 1 Silicon powder (purity 4N, average particle size 300μm, high purity chemical), metal ruthenium (purity 99.9%, average particle size 150μm, Furuuchi Chemical), and boron powder (purity 99%, average particle size 48μm, Furuuchi Chemical) were mixed with Si / (Ru+Si+B)=49atm%, Ru / (Ru+Si+B)=49atm%, and B / (Ru+Si+B)=2atm%, and then filled into a water-cooled mold and arc melted. The obtained raw material lump was crushed in an agate mortar using a mortar. After passing the powder through a 150μm sieve, it was filled into a circular spark plasma sintering mold with a size of 10mmφ and spark plasma sintering was performed. The sintering conditions were a sintering temperature of 1400℃, held for 10 minutes, and a pressure of 25MPa. The degree of vacuum was 6.0e-3Pa.
[0044] As a result of EBSD measurement, a space group 198 crystal phase was observed in the obtained alloy sample, which was a mixture of a space group 60 crystal phase of 4.6% by area and a space group 59 crystal phase of 0.2% by area.
[0045] The alloy samples were then processed to a size of 10 mmφ×1 mmt and used to measure electrical properties and thermal conductivity. The measurements were performed at 50°C in a vacuum. The results are shown in Table 1.
[0046] Example 2 Silicon powder (purity 4N, average particle size 300μm, manufactured by Kojundo Chemical), metal ruthenium (purity 99.9%, average particle size 150μm, manufactured by Furuuchi Chemical), boron powder (purity 99%, average particle size 48μm, manufactured by Furuuchi Chemical) were used with Si / (Ru+Si+B)=49atm%, Ru / (Ru+Si+B)=49atm%, B / (Ru+Si+B)=2atm%, the sintering temperature was 1400℃, it was held for 10 minutes, and the pressure was 75MPa. The other conditions were the same as those of Example 1.
[0047] Example 3 The experiment was performed under the same conditions as in Example 1, with silicon powder (purity 4N, average particle size 300 μm, High Purity Chemical), metallic ruthenium (purity 99.9%, average particle size 150 μm, Furuuchi Chemical), and boron powder (purity 99%, average particle size 48 μm, Furuuchi Chemical) set at Si / (Ru+Si+B)=48.5 atm%, Ru / (Ru+Si+B)=48.5 atm%, and B / (Ru+Si+B)=3 atm%.
[0048] Example 4 Silicon powder (purity 4N, average particle size 300μm, high purity chemical), metal ruthenium (purity 99.9%, average particle size 150μm, Furuuchi Chemical), boron powder (purity 99%, average particle size 48μm, Furuuchi Chemical) were used with Si / (Ru+Si+B)=48.5atm%, Ru / (Ru+Si+B)=48.5atm%, B / (Ru+Si+B)=3atm%, sintering temperature was 1400℃, held for 10 minutes, pressure was 75MPa. Other conditions were the same as those of Example 1.
[0049] Example 5 The experiment was performed under the same conditions as in Example 1, with silicon powder (purity 4N, average particle size 300 μm, high purity chemical), metallic ruthenium (purity 99.9%, average particle size 150 μm, Furuuchi Chemical), and boron powder (purity 99%, average particle size 48 μm, Furuuchi Chemical) with Si / (Ru+Si+B)=49.5 atm%, Ru / (Ru+Si+B)=49.5 atm%, and B / (Ru+Si+B)=1 atm%.
[0050] Example 6 Silicon powder (purity 4N, average particle size 300μm, high purity chemical), metal ruthenium (purity 99.9%, average particle size 150μm, Furuuchi Chemical), boron powder (purity 99%, average particle size 48μm, Furuuchi Chemical) were used with Si / (Ru+Si+B)=49.5atm%, Ru / (Ru+Si+B)=49.5atm%, B / (Ru+Si+B)=1atm%, sintering temperature was 1400℃, held for 10 minutes, pressure was 75MPa. Other conditions were the same as those of Example 1.
[0051] Example 7 The experiment was performed under the same conditions as in Example 1, with silicon powder (purity 4N, average particle size 300 μm, high purity chemical), metallic ruthenium (purity 99.9%, average particle size 150 μm, Furuuchi Chemical), and boron powder (purity 99%, average particle size 48 μm, Furuuchi Chemical) with Si / (Ru+Si+B)=47.5 atm%, Ru / (Ru+Si+B)=47.5 atm%, and B / (Ru+Si+B)=5 atm%.
[0052] Example 8 Silicon powder (purity 4N, average particle size 300μm, high purity chemical), metal ruthenium (purity 99.9%, average particle size 150μm, Furuuchi Chemical), boron powder (purity 99%, average particle size 48μm, Furuuchi Chemical) were used with Si / (Ru+Si+B)=47.5atm%, Ru / (Ru+Si+B)=47.5atm%, B / (Ru+Si+B)=5atm%, sintering temperature was 1400℃, held for 10 minutes, pressure was 75MPa. Other conditions were the same as those of Example 1.
[0053] Example 9 The experiment was performed under the same conditions as in Example 1, with silicon powder (purity 4N, average particle size 300 μm, high purity chemical), metallic ruthenium (purity 99.9%, average particle size 150 μm, Furuuchi Chemical), and boron powder (purity 99%, average particle size 48 μm, Furuuchi Chemical) with Si / (Ru+Si+B)=45 atm%, Ru / (Ru+Si+B)=45 atm%, and B / (Ru+Si+B)=10 atm%.
[0054] Example 10 Silicon powder (purity 4N, average particle size 300μm, high purity chemical), metal ruthenium (purity 99.9%, average particle size 150μm, Furuuchi Chemical), boron powder (purity 99%, average particle size 48μm, Furuuchi Chemical) were used with Si / (Ru+Si+B)=45atm%, Ru / (Ru+Si+B)=45atm%, B / (Ru+Si+B)=10atm%, sintering temperature was 1400℃, held for 10 minutes, pressure was 75MPa. Other conditions were the same as those of Example 1.
[0055] [Table 1]
[0056] (Reference example 1) The raw materials were Si / (Ru+Si+B)=50atm%, Ru / (Ru+Si+B)=50atm%, and the other conditions were the same as in Example 1. The results are shown in Table 2.
[0057] (Reference example 2) The raw materials were Si / (Ru+Si+B)=50atm%, Ru / (Ru+Si+B)=50atm%, the sintering temperature was 1400°C, the pressure was 75MPa, and the other conditions were the same as those in Example 1.
[0058] [Table 2]
[0059] The alloy materials of Examples 1 to 10 have both improved Seebeck coefficients and electrical conductivities compared to the alloy materials of Reference Examples 1 and 2, and can be used to fabricate highly efficient thermoelectric conversion elements. [Industrial Applicability]
[0060] By using the present invention, it is possible to fabricate a high-performance thermoelectric conversion element, and to efficiently utilize waste heat in a relatively low temperature range.
Claims
1. A silicide-based alloy material containing silicon and ruthenium as main components and containing boron, the atomic ratio of the elements constituting the alloy material being Si, Ru, and B, respectively. 45 atm%≦Si / (Ru+Si+B)≦49.5 atm% 45 atm%≦Ru / (Ru+Si+B)≦49.5 atm% 1 atm%≦B / (Ru+Si+B)≦10 atm% A silicide-based alloy material.
2. 2. The silicide-based alloy material according to claim 1, which is a silicide-based alloy material containing silicon and ruthenium as main components and containing boron, and has a plurality of crystal phases in its structure.
3. 3. The silicide-based alloy material according to claim 1, which is a silicide-based alloy material mainly composed of silicon and ruthenium and containing boron, and has at least two or more types of crystal phases selected from space groups 198, 60 and 59 in its structure.
4. A thermoelectric conversion element using the silicide-based alloy material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Thermoelectric material
JP2002368291A
P-type thermoelectric material, and its manufacturing method
JP2008147261A
Thermoelectric power generator
JP2010200520A
Silicide alloy material and element including the same
JP2019218592A
Silicide alloy material and element in which the same is used
JP2021020842A